Nanogold Functionalized With Lipoamide-isoDGR: A Simple, Robust and Versatile Nanosystem for αvβ3-Integrin Targeting - Sacchi, Angelina; Gasparri, Anna Maria; Monieri, Matteo; Anderluzzi, Giulia; Colombo, Barbara; Gori, Alessandro; Corti, Angelo; Curnis, Flavio (Frontiers in Chemistry, 2021)
Gold nanoparticles functionalized with isoDGR, a tripeptide motif that recognizes αvβ3 integrin overexpressed in tumor vessels, have been used as nano-vectors for the delivery of cytokines to tumors. Functionalization of nanogold with this peptide has been achieved by coating nanoparticles with a peptide-albumin conjugate consisting of heterogeneous molecules with a variable number of linkers and peptides. To reduce nanodrug heterogeneity we have designed, produced and preclinically evaluated a homogeneous and well-defined reagent for nanogold functionalization, consisting of a head-to-tail cyclized CGisoDGRG peptide (iso1) coupled via its thiol group to maleimide-PEG11-lipoamide (LPA). The resulting iso1-PEG11-LPA compound can react with nanogold via lipoamide to form a stable bond. In vitro studies have shown that iso1, after coupling to nanogold, maintains its capability to bind purified αvβ3 and αvβ3-expressing cells. Nanogold functionalized with this peptide can also be loaded with bioactive tumor necrosis factor-α (TNF) to form a bi-functional nanodrug that can be stored for three days at 37°C or >1 year at low temperatures with no loss αvβ3-binding properties and TNF-cytolytic activity. Nanoparticles functionalized with both iso1 and TNF induced tumor eradication in WEHI-164 fibrosarcoma-bearing mice more efficiently than nanoparticles lacking the iso1 targeting moiety. These results suggest that iso1-PEG11-LPA is an efficient and well-defined reagent that can be used to produce robust and more homogeneous nano-vectors for the delivery of TNF and other cytokines to αvβ3 positive cells.